دراسة مقارنة للاستخدام المتشابه في قصائد أبي العلاء المعري وسعدي الشيرازي - بيكي، محمد رضا; تبار، فرشته آزاد (جامعة الكوفة - كلية الآداب, 2019)
يلعب التشابه كعنصر الخيال الرئيسي دوراً كبيراً في إنشاء مجموعة متنوعة من الصور الشعرية. أبو العلا معاري وسعدي شيرازي شاعران عربيان وإيرانيان كانا قادرين على التألق في مجال الشعر خلال وقتهما. تهدف هذه الدراسة إلى التحقق من تشابه الصناعة البلاغية من خلال مقاربة وصفية تحليلية تستند إلى مدرسة الأدب المقارن الأمريكية من خلال سقط الزند معري وديوان سعدي. وخلصت إلى أن كلا الشاعرين قد نجحا في توضيح بعض المفاهيم الملموسة لمجموعة متنوعة من أوجه التشابه ونجحت في تشابههما في شعرهما، لكن معري جعل أكثر إبداعاً من سعدي في خلق الرموز الأصلية التي ولدت خيال الشاعر.
In an overview of the similar structure in Abi El-Ela Maari and Saadi Shirazi, it was found that the use of resemblance in the poetry of these two poets plays an important role in creating the style of the hair of al-Ma'ri and al-Sa'di. In this application, with a difference in the fall of the gendarme, the direction of the narrator is more analogous to the consonant, and in Saadi's poetry the poet's tendency is closer to the eloquent analogy. The analogous use of other poetic images has created a sort of personal style for two poets, the style of imaginative images in the context of technical and intangible vocabulary. There are many similarities and evidences in the poetry of these poets. A striking point is that the two pseudo-poets in many similarities of both poets are senses.
Keywords: الشعر العربي -- الصور الشعرية -- التشبيه -- المعري، أبو العلاء -- الشيرازي، سعدي